STRATEGI MANAJEMEN SUMBER DAYA MANUSIA DALAM MENGHADAPI TANTANGAN PENDIDIKAN ISLAM DI ERA DIGITAL - Fauza Yanuarti Pertiwi; Zainal Berlian; Baharudin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The massive wave of digital transformation has urged Islamic educational institutions to undertake comprehensive renewal in their human resource management systems in order to remain relevant and competitive in the modern era. This study aims to analyze the challenges of human resource management in Islamic education during the digital era, formulate appropriate and applicable management strategies, and identify the role of Islamic values as the primary foundation for holistic and characterful human resource management. This research employs a qualitative approach using the library research method, where data were collected selectively from reputable literary sources through Google Scholar, SINTA, and Scopus databases. The findings reveal that digital literacy gaps, shifting work paradigms caused by digitalization, as well as data ethics and security concerns, represent the primary challenges currently faced by Islamic educational institutions. The implementation of technology-based systems such as HRIS, E-HRM, and LMS has proven effective in significantly improving the effectiveness, transparency, and professionalism of human resource management. The integration of Islamic values including trust, justice, deliberation, and excellence into digital HRM systems serves as a strategic differentiator that strengthens the institutional identity and integrity of Islamic education. Transformational leadership that is strong and rooted in Islamic character remains the decisive factor in sustaining the successful and dignified implementation of all human resource management strategies.